Factors influencing non-communicable disease policy process in Sub-Saharan Africa: a scoping review - Bey-Marrié Schmidt; Connie Hoe; Solange Mianda; Shannon McMahon; Joy Mauti; Enny Brouns; Chanelle Mulopo (BMJ Public Health)
Introduction Non-communicable diseases (NCDs) have been the leading global cause of death for two decades, with a disproportionate impact on low- and middle-income countries. Despite the development of technical packages such as the WHO Best Buys, the adoption and implementation of NCD policies pose significant challenges. This scoping review explores the factors influencing the NCD policy process, including agenda setting, formulation, adoption, implementation and evaluation stages.Methods This scoping review followed the methodological framework provided by Levac et al. To identify relevant studies for the scoping review, we searched the literature in the following databases: Web of Science and Scopus using PubMed. Reviewers independently screened titles, abstracts and full texts, and extracted data from the included studies. The results were collected using Excel and synthesised using descriptive numerical and thematic analysis.Results The search yielded 7538 records, after screening for title, abstract and full text, 35 articles met the inclusion criteria for this review. Six different types of policy actors were identified, namely, (i) government, (ii) private sector, (iii) advocates, (iv) experts, (v) international partners, (vi) experts and (vii) general public. Policy actors used lobbying tactics to influence how the policy process was executed; however, it was unclear how the process of influence took place. We identified six barriers of the NCD policy process: (i) limited access to resources, (ii) limited reliable local data, (iii) role of the government, (iv) limited multisectoral collaboration, (v) limited infrastructure, (vi) knowledge and belief. Six facilitators of the NCD policy process were identified: (i) multisectoral approach, (ii) sufficient capacity and financial resources, (iii) access to reliable local evidence, (iv) strong advocacy, (v) existing infrastructures, and (vi) political will were reported.Conclusion Findings from this review revealed a knowledge gap in understanding of the tactics used by actors to influence the policy process and the absence of evidence related to the evaluation of NCD policies in Sub-Saharan Africa.